Odin og Ordet - Backhausen, Kirsten (Religionsvidenskabeligt Tidsskrift, 2001)
The Norse god Odin reigns over wisdom and poetry and thereby over language itself. Wisdom and language are joined together in the mead of poetry and several myths are concerned with the way Odin gains access to the mead. Mead is an intoxicating drink but the intoxication is first and foremost leading to a higher state of consciousness. The mead of poetry undergoes several transformations before it can be put to use, and linked to these transformations is the whole complex of death, rebirth and initiation. Mead and wisdom are drawn from the underworld and then symbolically reborn in the upper world, either through the mouth of Odin or by Odin undergoing a rite of initiation where he himself is reborn. Odin travels between the realms of the world and while travelling he brings mead, runes and wisdom from the underworld to the upper world. All these are connected to the word, and by supplying wisdom as well as the words to use in order to grasp that wisdom, he makes sure that the wisdom can be put to constructive use. By putting experiences into words you obtain a conscious understanding of their meanings and thereby an ability to act upon the obtained knowledge. With the words Odin opens a channel between the two realms of the world, but he keeps a few words and magic chants to himself. Thereby he remains the master of the channel and makes sure that the two realms do not collapse into one with chaos as the result